Assessment of vocal intensity in lecturers depending on acoustic properties of lecture rooms - Witold Mikulski (Nofer Institute of Occupational Medicine, 2015)
Background: Lombard's effect increases the level of vocal intensity in the environment, in which noise occurs. This article presents the results of the author's own study of vocal intensity level and A-weighted sound pressure level of background noise during normal lectures. The aim of the study was to define whether above-mentioned parameters depend on acoustic properties of rooms (classrooms or lecture rooms) and to define how many lectors speak with raised voice. Material and Methods: The study was performed in a group of 50 teachers and lecturers in 10 classrooms with cubature of 160-430 m3 and reverberation time of 0.37-1.3 s (group A consisted of 3 rooms which fulfilled, group B consisted of 3 rooms which almost fulfilled and group C consisted of 4 rooms which did not fulfill criteria based on reverberation time (maximum permissible value is 0.6-0.8 s according to PN-B-02151-4:2015). Criteria of raising voice were based on vocal intensity level (maximum value: 65 dB according to EN ISO 9921:2003). The values of above-mentioned parameters were determined from modes of A-weighted sound pressure level distributions during lectures. Results: Great differentiation of vocal intensity level between lectors was found. In classrooms of group A lectors were not using raised voice, in group B - 21%, and in group C - 60% of lectors were using raised voice. Conclusions: It was observed that acoustic properties of classrooms (defined by reverberation time) exert their effect on lecturer's vocal intensity level (i.e., raising voice), which may contribute to the increased risk of vocal tract illnesses. The occurrence of Lombard's effect in groups of teachers and lecturers, conducting lectures in rooms, was evidenced. Med Pr 2015;66(4):487-496